Simulation framework development for helicopter mission analysis - Goulos, Ioannis; Mohseni, Martina; Pachidis, Vassilios; D’Ippolito, Roberto; Stevens, Jos (American Society of Mechanical Engineers (ASME), 2010)
Helicopter mission performance analysis has always been an important topic for the helicopter industry. This topic is now raising even more interest as aspects related to emissions and noise gain more importance for environmental and social impact assessments. The present work illustrates the initial steps of a methodology developed in order to acquire the optimal trajectory of any specified helicopter under specific operational or environmental constraints. For this purpose, it is essential to develop an integrated tool capable of determining the resources required (e.g. fuel burnt) for a given helicopter trajectory, as well as assessing its environmental impact. This simulation framework tool is the result of a collaborative effort between Cranfield University (UK), National Aerospace Laboratory NLR (NL) and LMS International (BE). In order to simulate the characteristics of a specific trajectory, as well as to evaluate the emissions that are produced during the helicopter’s operation within the trajectory, three computational models developed at Cranfield University have been integrated into the simulation tool. These models consist of a helicopter performance model, an engine performance model and an emission indices prediction model. The models have been arranged in order to communicate linearly with each other. The linking has been performed with the deployment of the OPTIMUS process and simulation integration framework developed by LMS International. The optimization processes carried out for the purpose of this work have been based on OPTIMUS’ built-in optimizing algorithms. A comparative evaluation between the optimized and an arbitrarily defined baseline trajectory’s results has been waged for the purpose of quantifying the operational profit (in terms of fuel required) gained by the helicopter’s operation within the path of an optimized trajectory for a given constraint. The application of the aforementioned methodology to a case study for the purpose of assessing the environmental impact of a helicopter mission, as well as the associated required operational resources is performed and presented.
Keywords: Simulation, Trajectories (Physics); Emissions; Fuels; Aerospace industry; Algorithms; Engines; Noise (Sound); Optimization